Dose-response relationship of blood flow restriction training on isometric muscle strength, maximum strength and lower limb extensor strength: A meta-analysis - Yang, Qun; He, Xin Jia; Li, Ying Duan; Zhang, Yong Zhi; Ding, Cong Shi; Li, Guo Xing; Sun, Jian (Frontiers in Physiology, 2022)
Objective: To perform a meta-analysis on the efficacy and dose-response relationship of blood flow restriction training on muscle strength reported worldwide. Methods: Thirty eligible articles with a total sample size of 468 participants were included in the meta-analysis. This study was performed using the method recommended by the Cochrane Handbook(https://training.cochrane.org/handbook), and the effect size was estimated using the standardized mean difference（SMD）and using RevMan 5.4 software. Results: The meta-analysis showed that blood flow restriction training increased the lower limb extensor muscle strength [SMD = 0.72, 95%; confidence interval (CI): 0.43 to 1.00, p < 0.01], knee extensor isokinetic torque [SMD = 0.51, 95% CI: 0.26 to 0.76, p < 0.01], knee flexor isokinetic torque [SMD = 0.55, 95% CI: 0.35 to 0.75, p < 0.01], and squat one-repetition maximum [SMD = 0.28, 95% CI: 0.01 to 0.55, p < 0.01]. There was no publication bias. Evaluation of dose-response relationship showed that the training load, mode, frequency, duration, and maximum cuff pressure affected the muscle function. Conclusions: blood flow restriction training significantly improved lower limb muscle strength, and the optimal training conditions consisted of a weight load smaller or equal to 30% of one-repetition maximum, training duration longer than 4 weeks, frequency of more than 3 times/week, and maximum cuff pressure lower than 200 mmHg.